Dynkin diagrams and spectra of graphs (São Paulo Journal of Mathematical Sciences, 2014)
Dynkin diagrams rst appeared in [20] in the connection with classication of simple Lie groups. Among Dynkin diagrams a special role is played by the simply laced Dynkin diagrams An, Dn, E6, E7 and E8. Dynkin diagrams are closely related to Coxeter graphs that appeared in geometry (see [8]). After that Dynkin diagrams appeared in many braches of mathematics and beyond, em particular em representation theory.